2018
DOI: 10.1026/1612-5010/a000242
|View full text |Cite
|
Sign up to set email alerts
|

Der Einfluss eines achtsamkeitsbasierten Trainingsprogramms auf die Emotionsregulation von Sportlerinnen und Sportlern

Abstract: Zusammenfassung. Diese Studie untersucht den Einfluss von Achtsamkeitstraining auf die Emotionsregulation von Sporttreibenden. In einem Prä-Post-Kontrollgruppendesign mit insgesamt 68 Versuchspersonen wurde getestet, ob ein Zusammenhang zwischen Achtsamkeit und dem Einsatz adaptiver (maladaptiver) Strategien der Emotionsregulation besteht. Das verwendete Programm (BATL, Berliner Achtsamkeitstraining zur Leistungsoptimierung) steigert die Achtsamkeit signifikant und nimmt dadurch einen indirekten Einfluss auf d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This means that affect regulation strategies can be applied to any component of the cycle of emotions. Although many affect regulation programs target multiple components to optimize effectiveness (e.g., Kittler et al, 2018 ), the focus is usually set on one particular component. For this reason, assigning the different strategies to the different components of the cycle of emotions provides a sound basis for classification.…”
Section: Affect Regulation Within the Cycle Of Emotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that affect regulation strategies can be applied to any component of the cycle of emotions. Although many affect regulation programs target multiple components to optimize effectiveness (e.g., Kittler et al, 2018 ), the focus is usually set on one particular component. For this reason, assigning the different strategies to the different components of the cycle of emotions provides a sound basis for classification.…”
Section: Affect Regulation Within the Cycle Of Emotionsmentioning
confidence: 99%
“…Within the sports context, similar programs have been developed to improve affect regulation (Kaufman et al, 2009;Jekauc et al, 2016). Along these same lines, it has also been shown that mindfulness training, which emphasizes awareness of one's affective states, leads to improvements in affect regulation skills in athletes (Kittler et al, 2018). It has also been shown that athletes who actively perceive and accept their emotions and affective states are more able to cope with pressure and are less prone to choking under pressure (Hill et al, 2010;Hill and Shaw, 2013).…”
Section: Affect Regulation Within the Cycle Of Emotionsmentioning
confidence: 99%